(untitled) (Journal of the College of Basic Education, 2022)
Diabetes is a complex group of diseases with a variety of causes. Diabetes results in abnormal levels of glucose in the blood stream for 20 sample diabetes patients. The main variables under study were ageandHbA1C are useful clinical tools regression relation was used in this study. This research include study importance of using multiple regression model to predicting the some variables like age and HbA1C that effect on diabetics with help of statistical package SPSS 22according to null hypothesis . In result show in F-value is 74,134 with 2(df) , 17degree tract show strongly significant and in T-test show T=0932 and p- value 0.365 then null hypothesis is reject and we have relation between age and diabetes T=3.115HbA1C , p- value =0.006 , T=4.046 and p-value =0.001 . Finally both age and HbA1C individually linear relation with diabetes.